Development of an Electromechanical Biomimetic Prosthesis Using 3d Printing: Initial Findings for Interphalangeal and Metacarpophalangeal Joints - Gomez-Arias, B (Institute of Electrical and Electronics Engineers Inc., 2024)
This study presents the design and preliminary evaluation of a biomimetic prosthetic hand, leveraging 3D printing. Constructed using PLA for bone structures obtained from CT scans and TPU A95 for ligaments, the prosthetic s kinematics were evaluated focusing on the index finger. Controlled by DC motors, its movements were analyzed using Kinovea software and a 240 fps camera. The results showed high correlation coefficients (R2 ≥ 0.92) for abduction, adduction, and phalange movements, with mean absolute errors ranging from -3.09° to 10.56°. These findings highlight the need for precise anatomical adjustments and confirm the prosthetic s efficacy in mimicking natural hand movements. This research advances the development of accessible, functional upper limb prosthetics, and underscores directions for enhancing their precision and functionality. © 2024 IEEE.